2008
DOI: 10.15760/trec.152
|View full text |Cite
|
Sign up to set email alerts
|

Using Archived ITS Data to Measure the Operational Benefits of a System-wide Adaptive Ramp Metering System

Abstract: Type of Report and Period CoveredFinal Report Sponsoring Agency Code Supplementary Notes AbstractA System-Wide Adaptive Ramp Metering (SWARM) system has been implemented in the Portland, Oregon metropolitan area, replacing the previous pre-timed ramp-metering system that had been in operation since 1981. SWARM has been deployed on six major corridors and operates during the morning and afternoon peak hours. This report presents results of a -before‖ and -after‖ evaluation of the performance of two freeway corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It enables an override of the locally-determined metering rates when necessary. A comprehensive evaluation study done in Denver, Colorado in 1988 and 1989, has shown that the central override is effective in mitigating congestion on the mainline if the speeds are less than 90 [km/h] [14].…”
Section: Cooperation Between On-rampsmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables an override of the locally-determined metering rates when necessary. A comprehensive evaluation study done in Denver, Colorado in 1988 and 1989, has shown that the central override is effective in mitigating congestion on the mainline if the speeds are less than 90 [km/h] [14].…”
Section: Cooperation Between On-rampsmentioning
confidence: 99%
“…These upstream on-ramps are categorized as "slave" on-ramps. The main idea is to exploit their queuing capacity in order to mitigate downstream congestions [14].…”
Section: Cooperation Between On-rampsmentioning
confidence: 99%
“…The Helper method normally cannot achieve the optimization of the entire system. For the SWARM methods, a good prediction model is essential for a successful implementation (Bertini and Hn, 2006), which is still under investigation in this current stage. For the Bottleneck method, considering its advantages such as real-time applicability, limited input parameter, and ease of implementation, it is selected in this paper as the base approach for enhancement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These ideas are realized in the SWAR M (Bertini et al, 2008) and the Bottleneck (Lipp et al, 1991;Hochbaum and Woeginger, 1999) algorithms.…”
Section: Introductionmentioning
confidence: 99%